2013
DOI: 10.1387/ijdb.130031nv
|View full text |Cite
|
Sign up to set email alerts
|

Classification, epidemiology and therapies for testicular germ cell tumours

Abstract: Testicular germ cell tumours (TGCT) account for between 1% and 1.5% of male neoplasms and 5% of urological tumours in general. They are classified broadly into Seminoma, which resemble primordial germ cells (PGCs), and Non-Seminoma, which are either undifferentiated (embryonal carcinoma) or differentiated (exhibiting a degree of embryonic (teratoma) or extra-embryonic (yolk sac choriocarcinoma) patterning). We present the current details of the latest classification, epidemiology and treatment aspects of TGCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 27 publications
1
47
0
2
Order By: Relevance
“…Incidence of 55 new cases per 100,000 males per year world-wide, and increase in number of diagnosed man with TC in US and other Western countries, makes it an important healthcare issue (1,2). The most affected subjects are young Caucasians (between age of 25 and 29 years) and some of the most rapid trends are observed in men of European descent, especially in Scandinavian countries (3).…”
Section: Abstract Background: the Ras Association Domain Family Protmentioning
confidence: 99%
“…Incidence of 55 new cases per 100,000 males per year world-wide, and increase in number of diagnosed man with TC in US and other Western countries, makes it an important healthcare issue (1,2). The most affected subjects are young Caucasians (between age of 25 and 29 years) and some of the most rapid trends are observed in men of European descent, especially in Scandinavian countries (3).…”
Section: Abstract Background: the Ras Association Domain Family Protmentioning
confidence: 99%
“…A testicular yolk sac tumor is a type of NSGCT (1,3). Testicular yolk sac tumors are common in children exhibiting testicular cancer, however, they are rarely observed in adults (4).…”
Section: Discussionmentioning
confidence: 99%
“…According to testicular cancer guidelines (1,3,25), the current patient presented with a stage III tumor, therefore a PEB chemotherapy regimen was proposed for treatment. Follow-up assessments including general condition, serum markers and PET-CT should be regularly performed following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TGCTs are the most frequently observed solid tumor among men aged between 15 and 35 years old (2). Additionally, it has been reported that the incidence of TGCTs has increased over the last 30-40 years (3).…”
Section: Introductionmentioning
confidence: 99%